Variations in presidential leadership in France. Issue 4 (December 2016) - Thiébault, Jean-Louis
Abstract The centerpiece of this analysis is about the variations in presidential leadership of the seven French presidents under the Fifth Republic. The analysis of the political conditions of the method of government aims to locate the type and the nature of the presidential leadership of each of the seven French presidents. The acquisition of presidential leadership effectively starts with the way leaders win office. They are elected by direct universal suffrage, and they have therefore a strong legitimacy. To the extent that presidential leadership is conceived as a special activity in terms of a president's ability to identify goals, to mobilize support and to bring about substantive change, these skills enable a president to perform these different tasks and to fulfill a successful leadership role. Developing and maintaining close relationships with other political actors provide the principal resources of a president. In France, the appointment of the prime minister, ministers and advisors is important, as well as relations with the high civil service. But, above all, the relations between the president and public opinion are of major importance in terms of authority and power. Finally, the reputation of a president depends on the ability to solve the problems facing the country. It is measured by opinion polls that provide the level of satisfaction felt by public opinion with regard to the policy of the president. Applying the concept of leadership through the three factors of skills, relations and reputations helps to understand the performance of French presidents. Only General de Gaulle was able to demonstrate a high level of leadership. He had a very strong presidential style, with great qualities of communication. Some even talked about his charisma. The leadership of General de Gaulle's successors suffered from the comparison. It seems that the most recent presidents are victims of the weakness, even perhaps the collapse, of their leadership.